Personality traits and digital challenges in Honduran adults: exploring the Dark and Light Triads’ influence on internet gaming disorder and technology-related conflicts - Mejía-Suazo, Claudio J.; Landa-Blanco, Miguel; Mejía-Suazo, Gliver Aarón; Martínez-Martínez, Carlos A. (Frontiers in Public Health, 2025)
IntroductionThe present study analyzed the effects of Light and Dark Triad traits scores on Internet Gaming Disorder, intrapersonal and interpersonal conflicts related to internet consumption, conflicts, and communicational emotional usage related to mobile phones. Light Triad traits include Faith in Humanity, Humanism, and Kantianism. Dark Triad traits include Machiavellianism, Narcissism, and Psychopathy.MethodsThe sample consisted of 450 adults of the Honduran population, of which 55.33% were women, and 44.67% were men, with an average mean age of 25.52 years (SD = 6.79).ResultsResults indicate that Machiavellianism and Psychopathy scores have significant effects over Internet Gaming Disorder scores. Intrapersonal conflicts related to internet consumption were negatively affected by Narcissism scores and positively affected by Machiavellianism. Psychopathy scores explained interpersonal conflicts related to internet consumption scores. On the other hand, conflicts related to mobile phone usage were negatively affected by Narcissism and Kantianism, while Machiavellianism had positive effects. Finally, communicational emotional usage related to mobile phones was significantly affected by Machiavellianism.DiscussionWhen comparing by respondent’s sex, Machiavellianism consistently emerges as a key predictor; however, its effects tend to be stronger in men. In contrast, Psychopathy, Kantianism, and Narcissism exhibit more sex-specific associations, influencing females and males differently across digital behaviors and conflicts.